Breaking Through the Wall of Occupational Fraud: A Systematic Literature Review - Pudjiwati, Arni; Utomo, Dwi Cahyo (E-Jurnal Akuntansi, 2024)
Occupational fraud is a significant threat to the integrity and sustainability of an organization. This study presents a systematic literature review on occupational fraud. This research uses the Scopus database without any year restrictions. Thirty-five articles were identified for further analysis. Our findings highlight a deep understanding of the motivations and driving factors behind fraudulent behavior, as well as the need for a holistic approach to managing occupational fraud. This research provides valuable insights for practitioners, researchers, and policymakers in their efforts to overcome the challenges organizations face in preventing and detecting occupational fraud. This research enriches the literature review on occupational fraud, which is still difficult to find.Kata Kunci: Literature Review, Occupational Fraud, Fraud Keywords: Literature Review; Occupational Fraud; Fraud